Data for: Andic soil properties and tephra layers hamper C turnover in Icelandic peatlands - selective dissolution of Al, Fe, Si and decomposition proxies ... - Möckel, Susanne Claudia; Erlendsson, Egill; Gísladóttir, Guðrún (Dryad, 2021)
Due to frequent volcanic activity and erosion of dryland soils, peatlands in Iceland receive regular additions of mineral aeolian deposits (tephra and eroded material). Therefore, their soils may develop not only histic, but also andic characteristics. Here we present data sets of a study that elucidates interactions between carbon characteristics and andic soil properties in Histosols of three Icelandic peatlands. The data sets contain information about the soil carbon structure derived by 13C NMR spectroscopy, andic soil properties based on selective dissolution of Al, Fe and Si, decomposition proxies C/N, δ13C and δ15N, information on total carbon and nitrogen content, dry bulk density, soil organic matter content and pH measured in deionised water and NaF solution. ... : 1. Description of methods used for collection/generation of data: 1.1 Soil Sampling ApproachThe research area is in Austur Húnavatnssýsla in northwest Iceland. Soil samples were collected from three peatlands along a north-south transect from the coast (Torfdalsmýri - TDM), via the lowlands (Tindar - TIN) to the highland fringe (Hrafnabjörg - HRAFN). At each peatland, one soil profile was excavated. Each profile contains well preserved tephra deposits from the Hekla 3 and Hekla 4 eruption. Pooled bulk soil samples were collected at 10 cm intervals down to a depth of 20 cm below the Hekla 4 tephra layer. Above and below the tephra layers, the sampling interval was reduced to 2 x 5 cm. 1.2 Laboratory analyses 1.2.1 Solid state 13C NMR spectroscopy Solid state 13C NMR spectroscopy was used to determine the chemical composition or structure of soil organic carbon (see e.g. Kögel-Knabner, 1997). 1.2.2 Dry Bulk Density, Soil Organic Matter, %C and %N, stable isotope ratios δ13C and δ15N The dry bulk density of the ...